A neural network algorithm for detection of GI angiectasia during small-bowel capsule endoscopy - Leenhardt, Romain; Vasseur, Pauline; Li, Cynthia; Saurin, Jean Christophe; Rahmi, Gabriel; Cholet, Franck; Becq, Aymeric; Marteau, Philippe; Histace, Aymeric; Dray, Xavier; Sacher-Huvelin, Sylvie; Mesli, Farida; et al. (Gastrointestinal endoscopy, 2019)
GI angiectasia (GIA) is the most common small-bowel (SB) vascular lesion, with an inherent risk of bleeding. SB capsule endoscopy (SB-CE) is the currently accepted diagnostic procedure. The aim of this study was to develop a computer-assisted diagnosis tool for the detection of GIA. Deidentified SB-CE still frames featuring annotated typical GIA and normal control still frames were selected from a database. A semantic segmentation images approach associated with a convolutional neural network (CNN) was used for deep-feature extractions and classification. Two datasets of still frames were created and used for machine learning and for algorithm testing. The GIA detection algorithm yielded a sensitivity of 100%, a specificity of 96%, a positive predictive value of 96%, and a negative predictive value of 100%. Reproducibility was optimal. The reading process for an entire SB-CE video would take 39 minutes. The developed CNN-based algorithm had high diagnostic performances, allowing detection of GIA in SB-CE still frames. This study paves the way for future automated CNN-based SB-CE reading softwares.